1998
DOI: 10.1016/s0022-5347(01)62458-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Epidermal Growth Factor Receptor in Urinary Bladder Cancer Metastases

Abstract: Bladder cancers frequently exhibit an increased number of epidermal growth factor receptors (EGFR) in comparison to normal urothelium. The EGFR could potentially be a target for toxic conjugates. The aim of our study was to compare the expression of EGFR in metastases with concurrent or primary tumour in the urinary bladder using immunohistochemical techniques and a monoclonal antibody. Tumour material from 20 patients was investigated. The majority (13/20) of the metastases were homogeneously stained and show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…The staining for EGFR in NU samples was faint and barely detectable, which has also been reported previously [8]. The staining for ERBB3 was distinct, whereas that for ERBB4 was strong.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The staining for EGFR in NU samples was faint and barely detectable, which has also been reported previously [8]. The staining for ERBB3 was distinct, whereas that for ERBB4 was strong.…”
Section: Discussionsupporting
confidence: 87%
“…In bladder cancer, amplifications or rearrangements in the EGFR gene are not frequently detected [5]. The proportion of patients with bladder cancer (over‐)expressing EGFR protein has been reported to be 27–86%[6–9]. Some studies have shown that expression of EGFR increases with T category and grade, but apparently in a nonlinear pattern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…58 Work by Bue et al in bladder cancer metastases has shown a positive correlation between the EGFR status of primary bladder tumours and associated metastases. 59 By targeting therapies at inhibition of EGFR not only would it be possible to attempt to improve prognosis in the treatment of primary EGFR expressing tumours but it may also be possible to selectively target EGFR expressing metastases, irrespective of the primary tumour's EGFR status.…”
Section: Manipulation Of Egfr Activitymentioning
confidence: 99%
“…In patients with bladder cancer EGFR expression is associated with primary tumour stage, and in selected studies appears to predict tumour recurrence, progression and patient survival [10–13]. Although the patterns and prognostic value of EGFR expression in metastatic urothelial tract cancer have not been established, there were strong EGFR immunostaining patterns in most (13/20) bladder cancer metastases in one study [14]. Therefore EGFR represents a potential therapeutic target in urothelial carcinoma [9].…”
Section: Introductionmentioning
confidence: 99%